Osilodrostat in Cushing's disease: the management of its efficacy and the pitfalls of post-surgical results. (24th November 2022) - Antonini, Simone; Brunetti, Alessandro; Zampetti, Benedetta; Boeris, Davide; Saladino, Andrea; Cesare Cozzi, Renato
Abstract : Summary: Osilodrostat is a novel, orally administered cortisol synthesis inhibitor, approved in 2020 by the European Medicines Agency (EMA) for the treatment of Cushing's syndrome in adults. A significant amount of the studies currently available in the literature focus on treatment in patients with Cushing's disease. However, data collected from patients treated with osilodrostat in real-life settings still represents a small entity. For this reason, in this article, we will discuss two real-life cases of patients with Cushing's disease treated with this drug. The first report is about a 35-year-old woman with an adrenocorticotrophic hormone (ACTH)-secreting adenoma. After non-curative trans-nasal-sphenoidal (TNS) surgery, due to a small remnant of the adenoma, medical therapy with osilodrostat achieved fast and effective biochemical and clinical response. During treatment, progressive increase of ACTH levels and an enlargement of the pituitary remnant were documented, with planned radiosurgical treatment. The second case reports a 32-year-old man diagnosed with Cushing's disease in 2020, who, after surgery refusal, started osilodrostat at progressively up-titrated doses, according to 24 h urinary free cortisol levels, up to 5 mg twice a day. With osilodrostat, the patient reached biochemical and clinical control of disease until TNS surgery in October 2021, with complete remission. The first post-surgical biochemical assessment was equivocal in spite of a transient clinical hypoadrenalism, reverted after 2 months with the restoration of physiological hypothalamic-pituitary-adrenal axis (HPA) function. Learning points: Osilodrostat is a potent oral drug viable for Cushing's disease as medical therapy when surgery is not feasible or remission cannot be reached. Osilodrostat proves to be a safe drug and its main adverse effect is hypoadrenalism, due to the adrenolytic action of the compound. Osilodrostat needs a very tailored approach in its clinical use because there is no correlation between the level of hypercortisolism pre-treatment and the dose required to reach disease control.